New disc excision procedure for low and mid rectal endometriosis nodules using combined transanal and laparoscopic approach. (July 2014) - Roman, H.; Tuech, J.‐J.
Abstract Aim Colorectal resection in women with endometriosis involving the low and mid rectum may result in a poorer outcome than conservative procedures. In this technical note we present a new technique for transanal full thickness disc excision of endometriosis nodules involving the rectum. Method The procedure is performed by combined laparoscopic and transanal routes. The former involves paring the area of the rectum infiltrated by the nodule, which is then made amenable to endoluminal removal using the Contour Transtar stapler to carry out a large disc excision. Results The technique can remove a specimen as large as 80 mm in diameter and can be applied to patients with infiltrating rectal endometrial nodules up to 10 cm from the anal margin and 50–60% of the rectal circumference. The procedure is probably less likely to lead to rectal stenosis and denervation than colorectal resection. Conclusion This technique of transanal rectal disc excision using the Contour stapler is suitable in patients with infiltrating deep endometriosis nodules of the lower and mid rectum. It avoids a low rectal resection with its potential complications and unfavourable function.